2017
DOI: 10.1021/acs.jafc.7b03354
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation in Banana Varieties Highlights the Role of Melatonin in Postharvest Ripening and Quality

Abstract: This study aimed to investigate the role of melatonin in postharvest ripening and quality in various banana varieties with contrasting ripening periods. During the postharvest life, endogenous melatonin showed similar performance with ethylene in connection to ripening. In comparison to ethylene, melatonin was more correlated with postharvest banana ripening. Exogenous application of melatonin resulted in a delay of postharvest banana ripening. Moreover, this effect is concentration-dependent, with 200 and 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(110 citation statements)
references
References 41 publications
14
96
0
Order By: Relevance
“…Melatonin retards leaf senescence in several plants including barley and detached apple leaves . In addition, melatonin is effective in maintaining the quality of postharvest fruits such as peach, banana, and litchi . For harvested green leafy vegetables such as Chinese flowering cabbage, leaf senescence is the most important factors affecting its shelf‐life and nutritional value during the postharvest storage and distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin retards leaf senescence in several plants including barley and detached apple leaves . In addition, melatonin is effective in maintaining the quality of postharvest fruits such as peach, banana, and litchi . For harvested green leafy vegetables such as Chinese flowering cabbage, leaf senescence is the most important factors affecting its shelf‐life and nutritional value during the postharvest storage and distribution.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In addition, melatonin is effective in maintaining the quality of postharvest fruits such as peach, banana, and litchi. [41][42][43] For harvested green leafy vegetables such as Chinese flowering cabbage, leaf senescence is the most important factors affecting its shelflife and nutritional value during the postharvest storage and distribution. In this work, we found that exogenous application of melatonin-alleviated senescence changes in Chinese flowering cabbage, with melatonin treatment maintaining a higher value of Fv/Fm and total chlorophyll content, while inhibiting the expression of chlorophyll catabolic and senescence marker genes.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, exogenous application of melatonin delays postharvest senescence in banana, strawberry, and peach fruits 16 18 . Therefore, melatonin treatment is proposed to positively regulate fruit ripening but negatively regulate fruit senescence, although the two processes are intrinsically linked 15 , 16 . However, melatonin also regulates fruit metabolism or abiotic resistance via interaction with other signaling molecules.…”
Section: Introductionmentioning
confidence: 96%
“…Melatonin promotes ripening and improves quality of climacteric tomato fruit during postharvest life 14 , and further proteomics analysis provides insights into the physiological and molecular mechanisms underlying melatonin-mediated tomato fruit ripening 15 . In banana, another typical climacteric fruit, melatonin is also an indicator for fruit ripening in various varieties 16 . By contrast, exogenous application of melatonin delays postharvest senescence in banana, strawberry, and peach fruits 16 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation